2014
DOI: 10.1155/2014/235426
|View full text |Cite
|
Sign up to set email alerts
|

Local Overexpression of V1a-Vasopressin Receptor Enhances Regeneration in Tumor Necrosis Factor-Induced Muscle Atrophy

Abstract: Skeletal muscle atrophy occurs during disuse and aging, or as a consequence of chronic diseases such as cancer and diabetes. It is characterized by progressive loss of muscle tissue due to hypotrophic changes, degeneration, and an inability of the regeneration machinery to replace damaged myofibers. Tumor necrosis factor (TNF) is a proinflammatory cytokine known to mediate muscle atrophy in many chronic diseases and to inhibit skeletal muscle regeneration. In this study, we investigated the role of Arg-vasopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…Worth noting, PLC activates Protein Kinase C family members, among which the theta isoform plays an important role in both muscle differentiation and disease (Marrocco et al, 2014, 2017; Lozanoska-Ochser et al, 2018). The potent pro-myogenic effect of vasopressin was further characterized in myogenic cells cultured in a serum-free medium, a “clean” experimental model that allowed us to establish that L6 myogenic cells express the vasopressin V1a receptor (V1a-R) and that vasopressin elicits a complex signal transduction response in these cells (Minotti et al, 1998; Scicchitano, 2002, 2005; Naro et al, 2003; Toschi et al, 2011; Costa et al, 2014b). Moreover, it was found that V1a-R expression is modulated during the differentiation of L6 cells, probably in a post-translational manner (Alvisi et al, 2008).…”
Section: Muscle As a Target Of Neurohypophyseal Hormonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Worth noting, PLC activates Protein Kinase C family members, among which the theta isoform plays an important role in both muscle differentiation and disease (Marrocco et al, 2014, 2017; Lozanoska-Ochser et al, 2018). The potent pro-myogenic effect of vasopressin was further characterized in myogenic cells cultured in a serum-free medium, a “clean” experimental model that allowed us to establish that L6 myogenic cells express the vasopressin V1a receptor (V1a-R) and that vasopressin elicits a complex signal transduction response in these cells (Minotti et al, 1998; Scicchitano, 2002, 2005; Naro et al, 2003; Toschi et al, 2011; Costa et al, 2014b). Moreover, it was found that V1a-R expression is modulated during the differentiation of L6 cells, probably in a post-translational manner (Alvisi et al, 2008).…”
Section: Muscle As a Target Of Neurohypophyseal Hormonesmentioning
confidence: 99%
“…In an in vivo mouse model of tumor necrosis factor (TNF)-inhibited muscle regeneration, the administration of vasopressin rescued the inhibitory effect of TNF, likely through a mechanism involving the modulation of HSP70 levels (Moresi et al, 2009). Again, TNF-mediated muscle atrophy was rescued by the overexpression of the V1a-R in vivo (Costa et al, 2014b).…”
Section: Muscle As a Target Of Neurohypophyseal Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic and epigenetic regulatory mechanisms of myogenesis outlined above are exploited by the neurohypophyseal hormones AVP, oxytocin (OT), and related peptides, in their non-canonical role as potent inducers of myogenic differentiation in both in vitro and in vivo experimental models [3,9,18,19,20,21,22,23]. Indeed, we have previously shown that AVP induces myogenesis through a mechanism involving the transcriptional activation of myogenin at the MEF2 site of the myogenin promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Помимо него существуют свидетельства потенциально защитных влияний ВП, не позволяющие трактовать его роль как сугубо негативную. Так, известно, что снижение уровня ВП является существенным негативным фактором, приводящим к статистически значимо худшим исходам у пациентов с сосудистым шоком различной этиологии [11,12]. При этом, как показали исследования, ВП способен оказывать стимулирующее влияние на развитие мышечной ткани и противодействовать миодистрофии, вызванной другим важным медиатором негативного прогноза у пациентов с ХСН -фактором некроза опухолей альфа (ФНО-α) [13].…”
Section: Introductionunclassified